Cyclodextrin derivatives decrease Transient Receptor Potential vanilloid 1 and Ankyrin 1 ion channel activation via altering the surrounding membrane microenvironment by cholesterol depletion - Nehr-Majoros, Andrea Kinga; Erostyák, János; Fenyvesi, Éva; Szabó-Meleg, Edina; Szőcs, Levente; Sétáló, György; Helyes, Zsuzsanna; Szőke, Éva (Frontiers in Cell and Developmental Biology, 2024)
Transient Receptor Potential Vanilloid 1 (TRPV1) and Ankyrin 1 (TRPA1) are nonselective cation channels expressed in primary sensory neurons and several other non-neuronal structures such as immune cells, keratinocytes, and vascular smooth muscle cells. They play important roles in nociception, pain processing and their chanellopathies are associated with the development of several pathological conditions. They are located in cholesterol-and sphingolipid-rich membrane lipid raft regions serving as platforms to modulate their activations. We demonstrated earlier that disruption of these lipid rafts leads to decreased TRP channel activation and exerts analgesic effects. Cyclodextrins (CDs) are macrocyclic molecules able to form host-guest complexes with cholesterol and deplete it from the membrane lipid rafts. The aim of this study was to investigate 8 structurally different (methylated and non-methylated) CD derivatives on cell viability, mitochondrial membrane potential, membrane composition and activation abilities of the TRPV1 and TRPA1 channels. We showed that non-methylated derivatives have preferable safety profiles compared to methylated ones. Furthermore, methylated derivatives reduced mitochondrial membrane potential. However, all investigated derivatives influence the ordered cell membrane structure depleting membrane cholesterol and inhibit the TRPV1 agonist capsaicin-and the TRPA1 agonist allyl isothiocyanate-induced Ca 2+-influx. This mechanism of action might provide novel perspectives for the development of peripherally acting analgesics via indirectly decreasing the generation and transmission of nociceptive signals.